2011
DOI: 10.1007/s10637-011-9685-6
|View full text |Cite
|
Sign up to set email alerts
|

Salinomycin, a p-glycoprotein inhibitor, sensitizes radiation-treated cancer cells by increasing DNA damage and inducing G2 arrest

Abstract: Salinomycin (Sal) is potentially useful for the treatment of cancer. The present study examined a novel mechanism of Sal sensitization in cancer cells. Sal sensitized radiation-treated cancer cells by inducing G2 arrest and causing DNA damage. Sal treatment also reduced p21 levels in radiation-treated cells. Considering that Sal sensitizes doxorubicin (DOX)- or etoposide (ETO)-treated cancer cells by causing DNA damage and reducing p21 expression, the results from our study suggest that the mechanism underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 28 publications
1
48
0
Order By: Relevance
“…It is a lipophilic, anionic and weakly acidic compound with the molecular formula C 42 H 70 O 11 [1][2][3] . SAL has been shown to target Cancer Stem Cells (CSCs) in different types of human cancers, including gastric cancer [4], lung [5], osteosarcoma [6], colorectal cancer [3]., squamous cell carcinoma (SCC) [7], and prostate CSCs [8] mainly by inhibiting wnt signalling pathway [9][10][11][12][13]. SAL is able to enhance the cytotoxic effects of conventional anti cancer drugs such as doxorubicin, gemcitabine, etoposide, paclitaxel, docetaxel, vinblastine, and trastuzumab, envisioning a central role for SAL-based combination therapies in the future treatment of cancer [10,[14][15][16][17] One important caveat for developing SAL as a clinical treatment for cancer is the paucity of preclinical metabolism and pharmacokinetic data.…”
Section: Introductionmentioning
confidence: 99%
“…It is a lipophilic, anionic and weakly acidic compound with the molecular formula C 42 H 70 O 11 [1][2][3] . SAL has been shown to target Cancer Stem Cells (CSCs) in different types of human cancers, including gastric cancer [4], lung [5], osteosarcoma [6], colorectal cancer [3]., squamous cell carcinoma (SCC) [7], and prostate CSCs [8] mainly by inhibiting wnt signalling pathway [9][10][11][12][13]. SAL is able to enhance the cytotoxic effects of conventional anti cancer drugs such as doxorubicin, gemcitabine, etoposide, paclitaxel, docetaxel, vinblastine, and trastuzumab, envisioning a central role for SAL-based combination therapies in the future treatment of cancer [10,[14][15][16][17] One important caveat for developing SAL as a clinical treatment for cancer is the paucity of preclinical metabolism and pharmacokinetic data.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Sal may also sensitize cancer cells to radiation or to cytostatic drugs, such as etoposide or doxorubicin, by increasing apoptosis as a result of enhancing DNA damage and reducing the levels of CDKN1A/p21 protein. [19][20][21] Evidence is emerging that Sal inhibits WNT-CTNNB1/β-catenin signaling by inducing WNT coreceptor lipoprotein receptor related protein 6 (LRP6) degradation. 22,23 In addition, Sal leads to an increase of cytosolic Ca 2+ through the Na + /Ca 2+ exchangers in the plasma membrane and mitochondria, and induces calpain and cytochrome c-mediated neuronal cell death.…”
mentioning
confidence: 99%
“…This finding is noticeable because others have demonstrated that treatment with Salinomycin in equal concentrations is associated with accumulation in the pre-G1-phase, indicating increased apoptosis [17] Furthermore, in pre-treated human breast cancer with antimitotic drugs, Salinomycin abolishes G2-arrest and aneuploid cell formation [17,40]. In contrast, radiationtreated breast cancer cells accumulate in the G2-phase after treatment with Salinomycin [41]. Interestingly, Salinomycin-induced apoptosis in human leukemia cells is not accompanied by cell cycle arrest at all [20].…”
Section: Discussionmentioning
confidence: 96%